Imaging for treatment planning in lipo-and lymphedema - Zetzmann, Katharina; Ludolph, Ingo; Horch, Raymund E.; Boos, Anja (Handchirurgie, Mikrochirurgie, Plastische Chirurgie, 2018)
Lipoedema is a progressive disease, which predominantly affects women. It is characterised by circumferential growth, with increase in fat tissue of the extremities, and can lead to oedema. In contrast, the lymphoedema is defined by a specific lymphatic drainage disorder and can lead to fibrosis of the surrounding connective tissue. While lipoedema is diagnosed through clinical symptoms and diagnostic imaging can usually only be used to rule out comorbidities, lymphatic drainage disorder can be visualised using imaging methods. Ultrasound is a basis diagnostic tool to show retained interstitial fluid in lip- and lymphoedema. Lymphoscintigraphy is considered to be the gold standard to demonstrate a lymphatic drainage disorder, which can be combined with computed tomography. Indocyanine green(ICG) lymphography is a dynamic imaging tool, which is of increasing significance due to its possible intraoperative use. Magnetic resonance imaging (MRI) lymphography has the ability to visualise a lymphoedema and a lymphatic drainage disorder in three dimensions and is therefore considered to be a meaningful supplement. Therapy of lip- and lymphoedema should always be based on a combination of conservative and surgical strategies. While liposuction and other resection procedures can lead to symptom relief in lipedoema or advanced lymphoedema, newer reconstructive procedures such as lymph node transplantation or lymphovenous anastomoses are modern techniques to treat lymphoedema. A long lasting volume reduction can be achieved by creating new lymphatic pathways leading to improved quality of life and reduced symptoms.
EVALuna2:211463